Linzagolix With and Without Hormonal Add-Back Therapy for the Treatment of Symptomatic Uterine Fibroids: Two Randomized, Placebo-Controlled, Phase 3 Trials. Issue 12 (December 2022) - Donnez, Jacques; Taylor, Hugh S.; Stewart, Elizabeth A.; Bradley, Linda; Marsh, Erica; Archer, David; Al-Hendy, Ayman; Petraglia, Felice; Watts, Nelson; Gotteland, Jean-Pierre; Bestel, Elke; Terrill, Paul; et al.
Abstract : (Abstracted from Lancet 2022;400:896–907) Uterine fibroids occur in 50% to 60% of women and are symptomatic in 30% of patients by causing abnormal uterine bleeding and pelvic pressure. Treatment of uterine fibroids involves surgical and radiological interventions, as well as progestogens and other medical therapies.